Post-graduate education students’ oral history research: A review of retired teachers’ experiences and perspectives of the former Bantu Education system (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Throughout the centuries, irrespective of the nature of the society or culture, social history seems to have been narrated or written by the victor glorifying his/her own cause.1 The voice of the ordinary person is rarely captured in standard historical works and consequently research in this area is certainly warranted and has currently become a vibrant field of research. With this article the author intends to fill one of these gaps in the narrative of social history and focuses specifically on the experiences of teachers who taught under a previous education system in South Africa, namely Bantu Education. As part of their studies in a History of Education honours course, students were required to conduct interviews with retired teachers (or teachers who had a significant number of years’ experience in Bantu Education) as part of their practical research. The interviews aimed to determine these teachers’ experiences and perceptions of teaching in the Bantu Education system. The collected data was analysed following Tesch’s method of qualitative data analysis. Although there was consensus among all the interviewees that Bantu Education was morally wrong and unjustifiable, the majority of the interviewees also identified positive experiences which call for consideration and reflection. The role of and need for conducting oral history interviews to provide a personalised perspective of past events is clear. Keywords: ;;; ;
Keywords: Oral history research; Post-graduate research project; Apartheid; Bantu Education; Retired teachers’ experiences Bantu Education